Increased Kremen2 predicts worse prognosis in colon cancer - Junxian Long; Junxian Long; Fengyun Cong; Fengyun Cong; Yousheng Wei; Jungang Liu; Jungang Liu; Weizhong Tang; Weizhong Tang (Frontiers Media S.A., 2023)
Background: Colon cancer (CC) is the fifth most prevalent cancer around the globe and poses a major risk to human health. Even though Kremen2 serves as a prognostic indicator in individuals with malignant tumours, its role in evaluating the prognosis of individuals with colon cancer has not been confirmed.Methods: Here, we examined the protein expression of Kremen2 in CC tissues and paired adjacent normal tissues by immunohistochemistry (IHC), then analyzed the clinical and RNA-seq data presented in The Cancer Genome Atlas (TCGA) database to confirm the relationship between Kremen2 levels and CC. In addition, the associations between Kremen2 mRNA expression and infiltrating immune cells were examined.Results: The study showed that the mRNA expression and protein level of Kremen2 were increased in CC tissues compared with adjacent normal tissues. According to Kaplan-Meier analysis, high Kremen2 expression in CC was linked to poor overall survival and progression-free survival. Clinical correlation analysis highlighted that a high level of Kremen2 expression was strongly linked with tumour progression, particularly lymph node metastasis. Cox regression analysis highlighted that Kremen2 was an independent prognostic indicator for CC. Bioinformatic studies highlighted that Kremen2 might be associated with the immune status in CC.Conclusion: Increased Kremen2 could serve as a potential prognostic CC biomarker.